The midwife-student mentor relationship: Creating the virtuous circle. Issue 5 (September 2022) - Sheehan, A.; Elmir, R.; Hammond, A.; Schmied, V.; Coulton, S.; Sorensen, K.; Arundell, F.; Keedle, H.; Dahlen, H.; Burns, E.
Abstract: Background: Good mentoring is important for students to support their adjustment to and learning in the clinical environment. The quality of the mentoring relationship is key for students but there is a lack of evidence explaining how a good mentor/mentee relationship establishes and develops over time. Aim: To explore the developing relationship between mentors and mentees participating in a structured midwifery mentoring program in one Local Health District in Sydney, Australia. Methods: A qualitative interpretive descriptive research design was utilised. Data were collected using 10 focus groups with midwife mentors (n = 31) and seven focus groups and four interviews with Bachelor of Midwifery student mentees (n = 24), over a 12-month period. Thematic analysis using an inductive approach was applied incorporating constant comparison to identify themes and sub-themes. Findings: Three overarching themes and three sub-themes were identified. The first theme was 'The great unknown'. Within the second theme 'Building the relationship' were three subthemes: trying to connect; becoming known; and an insider on your side . The final theme 'the virtuous circle' described the reciprocal relationship and benefits that developed between mentor and mentee. Discussion: The mentor/mentee relationship took time to develop and went through a number of phases. A positive mentor/ mentee relationship flattened hierarchical differences, increased student confidence and capacity for learning, and reflected the midwifery continuity of care relationship between midwife and woman built on respect and partnership. Conclusion: Developing a successful midwifery mentoring relationship takes persistence, reassurance, and mutual disclosure ultimately resulting in a recurring cycle of encouragement and support.